Specific and Selective Quantitation of Antiviral Drugs in the Presence of Impurities by Liquid Chromatography - NAVANEETHAN, G; KARUNAKARAN, K; ELANGO, K.P (Yàowu shi͡p︡in fenxi, 2012)
A stability indicating reversed phase high performance liquid chromatography method was developed and validated for the determination of the antiviral drugs of nevirapine, lamivudine and zidovudine in combination drug product. The chromatographic separation of nevirapine, lamivudine, zidovudine and eight specified impurities of thymine, thymidine, zidovudine related compound B, nevirapine related compound A, nevirapine related compound B, salicylic acid, cytosine, lamivudine diastereomer impurity were achieved with Waters symmetry C18 (250 mm × 4.6 mm i.d., 5 μm) column. The method was validated according to the ICH guidelines with respect to system suitability, linearity, precision, accuracy, robustness, LOD, LOQ, selectivity and specificity. Forced degradation study was also performed in tablet to demonstrate the stability indicating power of the optimized HPLC method. The samples were degraded in hydrogen peroxide condition indicating that the drug product is susceptible to oxidation. Statistical analysis proves that the method can be repeated and selective for the estimation of said drugs. The method could effectively separate the drug from its degradation product hence it can be used as a stability indicating method. This developed procedure is also applicable for the determination of instability of the drug and dissolution behaviour of the said products in commercial products.